TGFβ-specific T cells induced by a TGFβ-derived immune modulatory vaccine both directly and indirectly modulate the phenotype of tumor-associated macrophages and fibroblasts - Mads Hald Andersen; Inés Lecoq; Evelina Martinenaite; Maria Perez-Penco; Lucia Lara de la Torre (Journal for ImmunoTherapy of Cancer)
The tumor microenvironment (TME) of pancreatic cancer is highly immunosuppressive. We recently developed a transforming growth factor (TGF)β-based immune modulatory vaccine that controlled tumor growth in a murine model of pancreatic cancer by targeting immunosuppression and desmoplasia in the TME. We found that treatment with the TGFβ vaccine not only reduced the percentage of M2-like tumor-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs) in the tumor but polarized CAFs away from the myofibroblast-like phenotype. However, whether the immune modulatory properties of the TGFβ vaccine on TAM and CAF phenotypes are a direct consequence of the recognition and subsequent targeting of these subsets by TGFβ-specific T cells or an indirect consequence of the overall modulation induced within the TME remains unknown. Recognition of M2 macrophages and fibroblast by TGFβ-specific T cells was assessed by ELISpot and flow cytometry. The indirect and direct effects of the TGFβ vaccine on these cell subsets were evaluated by culturing M2 macrophages or fibroblasts with tumor-conditioned media or with T cells isolated from the spleen of mice treated with the TGFβ vaccine or a control vaccine, respectively. Changes in phenotype were assessed by flow cytometry and Bio-Plex multiplex system (Luminex). We found that TGFβ-specific T cells induced by the TGFβ vaccine can recognize M2 macrophages and fibroblasts. Furthermore, we demonstrated that the phenotype of M2 macrophages and CAFs can be directly modulated by TGFβ-specific T cells induced by the TGFβ vaccine, as well as indirectly modulated as a result of the immune-modulatory effects of the vaccine within the TME. TAMs tend to have tumor-promoting functions, harbor an immunosuppressive phenotype and are linked to decreased overall survival in pancreatic cancer when they harbor an M2-like phenotype. In addition, myofibroblast-like CAFs create a stiff extracellular matrix that restricts T cell infiltration, impeding the effectiveness of immune therapies in desmoplastic tumors, such as pancreatic ductal adenocarcinoma. Reducing immunosuppression and immune exclusion in pancreatic tumors by targeting TAMs and CAFs with the TGFβ-based immune modulatory vaccine emerges as an innovative strategy for the generation of a more favorable environment for immune-based therapies, such as immune checkpoint inhibitors.